Development of a 18F-labelled carborane-peptide conjugate for Boron neutron capture therapy (BNCT) - Narangoda Kankanamalage Dona, Asanka (My University, 2026)
Brain tumors are heterogeneous group of neoplasms that could arise within the brain and are associated with considerable morbidity and mortality, due to unregulated cellular proliferation, aggressive biological behavior, and significantly resistant to conventional treatments. Blood brain barrier (BBB) is one of a major challenge which substantially restrict or prevent the delivery of many diagnostic and chemotherapeutic agents to the central nervous system. Boron neutron capture therapy (BNCT) is a targeted therapeutic strategy that based on the selective accumulation of boron-10 compounds in the tumor cells. In this research the boron delivery agent is FNA-S-ACooP which is a novel peptide-based radiotracer and also binding to FABP3 (fatty acid binding protein).The aim of this research was to develop a novel boron carrier, based on the ACooP (H-ACGLSGLGVA-NH2) a linear decapeptide and which can be radiolabelled with fluorine-18 for diagnostic purposes. In parallel, ACooP is a brain tumour homing peptide and is recognized for fatty acid binding protein as well as mammary derived growth -inhibitor. In this research, FNA-S-ACooP and the carborane moiety contributes significantly as all the conjugations are based on this carborane-peptide scaffold structure. In the synthesis of FNA-S-ACooP fluoronicotinic acid-4-nitrophenyl ester serves as the prosthetic group which has a high ability of conjugating with numerous biomolecules due to presence of activated ester. Previous investigations revealed that all published reports related to conjugations between FNA, and biomolecules indicated N acylated derivatives except the conjugation with AcooP peptide. Therefore, as the first step of the reaction scheme it was successfully synthesis and characterized FNA-S-ACooP. The reaction was carried out under borate buffer with 70% of acetonitrile under 8.3 pH for 10 min and yielded FNA-S-ACooP with 62.3 %. The initial approach was direct carborane-peptide conjugation, but unfortunately the reaction did not result and unable to characterized to correct product. As the second approach it was decided to investigate conjugation of the carborane to the peptide by using a PEGylated linker. FNA-S-ACooP was first reacted with Azido-PEG-NHS-ester to give FNA-S-ACooP-N-PEG2-N3. Upon the first attempt it resulted product, but it was observed that the conjugation efficiency has been mitigated, during the reaction. Therefore, to overcome this barrier it was required to enhance the accessibility of the active sites of the reactants. Simultaneously, it became evident that it is necessary of purifying the product and the reactants with formic acid over trifluoro acetic acid in order to enhance the accessibility of reaction sites. Following the modification FNA-S-ACooP-N-PEG2-N3 yielded with 76.8 %. The subsequent step involved the integration of carborane moiety to the peptide back bone and eventually to synthesize the target compound carborane-N-FNA-S-ACooP with azido functionalized peptide via copper catalysed 1,3-dipolar cycloaddition. However, the incorporation of carborane cluster to propargyl-PEG3-amine reaction was not able to be optimised under the investigated condition. Therefore, the intended compound which is carborane-N-FNA-S-ACooP was not able to achieve. The synthesis procedure and the isolation and purification and characterization associated with considerable challenges. In conclusion, further optimization is needed in order to find optimal reaction conditions for conjugation of carborane to FNA-S-ACooP peptide.
Keywords: FNA-S-ACooP; BNCT; carborane; PET imaging; fluorine-18